Literature Review: Fraud Triangle Trends In Indonesia During 2016-2021 - Debora Lisa Afrianto; I Made Laut Mertha Jaya; Ratna Marta Dhewi (MASI Mandiri Edukasi, 2023)
Fraud is one of the behaviors that are a problem in every country, both in developing and developed countries. This study aims to review financial statement fraud research development to provide findings on financial statement fraud trends in Indonesia. Researchers used a qualitative method with literature review techniques on several journals indexed by google scholar, garuda, sinta 2, and sinta 4 during 2016-2021 in Indonesia. The total number of studies reviewed was 15 journals. This study concludes that the three elements of the fraud triangle impacted financial statement fraud for eight company sectors during 2016-2021. Pressure, followed by opportunity and rationalization, has the most substantial impact on financial statement fraud. Meanwhile, external pressure, organizational structure, change in auditor, and auditor opinion do not affect the occurrence of financial statement fraud. These findings open up opportunities for future research to present literature on studies with a broader range of sectors and other fraud analyses (fraud diamond, fraud pentagon, and fraud hexagon) in Indonesia. This research aims to provide findings in a literature review of financial statement fraud trends in Indonesia.